Pengaruh Metode Problem-Based Learning terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam di SMP NU Pakis: Pengaruh Metode Problem-Based Learning terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam di SMP NU Pakis - Asmaul Khusnah; Abdul Qodir; Khoirul Arifin; Abdurrahman (STIT Sirojul Falah Bogor, 2026)
Abstract: This study aims to measure the effect of the Problem-Based Learning (PBL) method on students' learning outcomes in Islamic Religious Education (PAI) at SMP NU Pakis. The study was motivated by the consistently low PAI learning outcomes among Grade VIII students who had not reached the Minimum Mastery Criteria (KKM), compounded by the dominance of conventional teaching methods and limited active student engagement. A quantitative approach with a quasi-experimental design was employed. Data were collected via questionnaire and documentation from 61 Grade VIII students (classes 8A Tahfidz and 8B Unggulan) in the 2025/2026 academic year. All questionnaire items were found to be valid, with acceptable reliability for the PBL variable (α = 0.577) and learning outcomes (α = 0.642). The Kolmogorov-Smirnov normality test confirmed normal data distribution (sig. 0.200 > 0.05). Simple linear regression analysis yielded a significant F-value (sig. 0.000 < 0.05), indicating that PBL exerts a simultaneous and significant effect on PAI learning outcomes. The findings suggest that PBL effectiveness is most evident when implemented comprehensively and collectively across instructional contexts. This research provides empirical contributions to the development of active learning methods within PAI in Islamic junior high schools. Keywords:Problem-Based Learning, Learning Outcomes, Islamic Religious Education, Active Learning, Islamic Junior High School